Fabrication of regular polystyrene foam structures with selective laser sintering. (December 2017) - Sun, Bingbing; Kulinsky, Lawrence
Graphical abstract: Highlights: FEA simulation demonstrates advantage of the regular foams over other cellular structures of the same effective density. The regular foam parts are fabricated out of polystyrene powder using multi-step Selective Laser Sintering process. The experimental compressive strength is lower than FEA simulated values due to granular structure of the real samples. Abstract: In the presented work, a procedure to fabricate regular polymer foams is proposed and demonstrated. Multi-step selective laser sintering (SLS) process (where unbound powder is cleared from each row of cavities before continuation of layer-by-layer build) is utilized to produce polystyrene parts with identical regularly spaced porosities. Mechanical compression testing was performed on the regular foam parts and on solid polystyrene parts with the same dimensions as the fabricated foam parts. Testing results indicate that the solid polystyrene samples have compressive strength in the range between 36.00 and 42.73 MPa, while less dense regular foam samples have compressive strength in the range between 27.85 and 39.38 MPa. The Young's modulus deduced from the stress-strain curves for solid samples is in the range between 779.2–879.0 MPa for solid samples and 771.3–885.9 MPa for the foam samples.